Modelling of fluorescent lamp characteristics - Lau, Pik Yew. (2011)
Fluorescent lamp is a low-pressure device. The major components of the fluorescent lamp are the electrodes (cathode and anode), low-pressure mercury droplet, argon gas and a phosphor coated glass tube. Fluorescent lamp overtook incandescent lamps as the major source of lighting in United States in 1952 because it was found to be more efficient and had longer life than incandescent lamp. Nowadays, fluorescent lamp can be found in almost every household. It is also widely used in automobile, emergency light source and portable lighting equipment.